Genome-wide identification of galactinol synthase (GolS) genes in Solanum lycopersicum and Brachypodium distachyon - ÖZYİĞİT, İBRAHİM İLKER (ELSEVIER SCI LTD, 2015)
GoIS genes stand as potential candidate genes for molecular breeding and/or engineering programs in order for improving abiotic stress tolerance in plant species. In this study, a total of six galactinol synthase (GolS)genes/proteins were retrieved for Solanum lycopersicum and Brachypodium distachyon. GolS protein sequences were identified to include glyco_transf_8 (PF01501) domain structure, and to have a close molecular weight (36.40-39.59 kDa) and amino acid length (318-347 aa) with a slightly acidic pI (5.35-6.40). The sub-cellular location was mainly predicted as cytoplasmic. S. lycopersicum genes located on chr 1 and 2, and included one segmental duplication while genes of B. distachyon were only on chr 1 with one tandem duplication. GoIS sequences were found to have well conserved motif structures. Cis-acting analysis was performed for three abiotic stress responsive elements, including ABA responsive element (ABRE), dehydration and cold responsive elements (DRE/CRT) and low-temperature responsive element (LTRE). ABRE elements were found in all GoIS genes, except for SIGoIS4; DRE/CRT was not detected in any GoIS genes and LTRE element found in SlGolS1 and BdGolS1 genes. AU analysis in UTR and ORF regions indicated that SlGolS and BdGoIS mRNAs may have a short half-life. SlGolS3 and SlG0lS4 genes may generate more stable transcripts since they included AATTAAA motif for polyadenylation signal POLASIG2. Seconder structures of SIGolS proteins were well conserved than that of BdGolS. Some structural divergences were detected in 3D structures and predicted binding sites exhibited various patterns in GoIS proteins. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Polyadenylation signal; Tandem duplication; Segmental duplication; mRNA longevity; MOLECULAR RESPONSES; STRESS TOLERANCE; EXPRESSION; DROUGHT; COLD; INITIATION; SALINITY; DATABASE; CLONING; RATES